Pre-Hispanic anthropogenic wetlands in the upper Ica drainage, south-central Andes: dating and context - (:unkn) unknown (Cambridge University Press, 2022)
Humans have engineered their environments throughout the Holocene, especially in the construction of hydraulic infrastructure. In many regions, however, this infrastructure is difficult to date, including the vestiges of water-management systems in the Andean highlands. Focusing on silt reservoirs in the upper Ica drainage, Peru, the authors use cores and radiocarbon dates to demonstrate the pre-Hispanic construction of walls to enhance and expand wetlands for camelid pasture. Interventions dated to the Inca period (AD 1400–1532) indicate an intensification of investment in hydraulic infrastructure to expand production capacity in support of the state. The results are discussed in the context of the hydraulic strategies of other states and empires.

Lane, K. J., Beresford Jones, D., Coll, L. V. J., Marsh, E. J., Scaife, R., Greco Mainero, M. C., Oros, O. H., Herrera, A., Grant Lett Brown, J. L. y French, C. (2022). Pre-Hispanic anthropogenic wetlands in the upper Ica drainage, south-central Andes: Dating and context. Antiquity, 96(389), 1251-1271.
Fil: Lane, Kevin John. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Fil: Beresford Jones, David. Universitat Bonn; Alemania
Fil: Coll, Luis Vicente Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Fil: Marsh, Erik Johnson. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina
Keywords: Peru; Ica drainage; Inca Empire; Anthropogenic wetland; Hydrological technology